Billolivia, a new genus of Gesneriaceae from Vietnam with five new species - Middleton, David; Atkins, Hannah; Truong, Luu Hong; Nishii, Kanae; Möller, Michael (Phytotaxa, 2014)
Based on molecular and morphological data, the new genus Billolivia with five new species, B. longipetiolata, B. minutiflora, B. poilanei, B. vietnamensis and B. violacea, is described. IUCN conservation assessments are provided for the species.